Identifying Facilitators and Barriers in Quebec Schools to Promote Inclusive Physical Education - Margaux Hebinck; Maxence Boisvert; Mariève Labbé; Roxanne Périnet-Lacroix; Jérémie Brisebois; Krista L. Best; Maxime T. Robert (Disabilities, 2023)
Inclusive physical education allows the development of social skills, attitudes, and awareness of peers about functional limitations and enhances the leadership skills of all children. However, the positive experience of children with functional limitations in inclusive physical education can be impacted by programs inadequate to their abilities and the limited training and knowledge of physical educators about teaching in consideration of their needs. The objective of this study was to identify the facilitators and barriers experienced by physical educators to include children with functional limitations in physical education in Quebec schools. A cross-sectional descriptive study with an online survey was conducted with physical education teachers and daycare educators. Descriptive statistics were used to analyze the data. A total of 149 participants (n = 130 physical education teachers) responded to the survey. Most respondents (79.5%) included children with functional limitations in activities with their classmates. However, 39.4% of respondents reported feeling not informed and not equipped to facilitate inclusion. This study identified the facilitators and barriers to physical education for children with functional limitations from the perspectives of physical educators, in Quebec schools, and the role of the latter to encourage inclusion.